COMIC AS A MEDIA FOR DENTAL AND ORAL HEALTH EDUCATION IN PRIMARY SCHOOL STUDENTS - Nganro, Reski; Adam, Arlin; Iskandar, Ishaq (Universitas Muhammadiyah Ponorogo, 2025)
Elementary school-age children often lack knowledge about dental and oral hygiene, leading to neglect in maintaining their health. To address this, engaging health promotion media, such as comics, can be utilized to enhance their understanding. This quasi-experimental study employed a two-group pre-test-post-test design with 87 elementary school students, divided into an experimental group (educated using comics) and a control group (educated using leaflets). A 20-question questionnaire assessed knowledge levels before and after the intervention. Results showed an increase in knowledge in both groups, with a significantly higher improvement in the comic group compared to the leaflet group. Unpaired T-test analysis confirmed a statistically significant difference (p=0.000, p<0.05), indicating that comics are more effective than leaflets in enhancing dental health knowledge. The study concludes that comic-based health promotion significantly improves oral hygiene awareness among elementary school children, suggesting its potential as an effective educational tool.